2008
DOI: 10.1016/j.ijrobp.2007.10.047
|View full text |Cite
|
Sign up to set email alerts
|

A Mitochondria-Targeted Nitroxide/Hemigramicidin S Conjugate Protects Mouse Embryonic Cells Against Gamma Irradiation

Abstract: Purpose-To evaluate the in vitro radioprotective effect of the mitochondria-targeted hemigramicidin S-conjugated 4-amino-2,2,6,6-tetramethyl-piperidine-N-oxyl (hemi-GS-TEMPO) 5-125 in γ-irradiated mouse embryonic cells and adenovirus-12 SV40 hybrid virus transformed human bronchial epithelial cells BEAS-2B and explore the mechanisms involved in its radioprotective effect.Methods and Materials-Cells were incubated with 5-125 before (10 minutes) or after (1 hour) γ-irradiation. Superoxide generation was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…We further attempted to validate the significance of the chemical/biochemical and computational predictions using a model of irradiation induced apoptosis in MECs [53] treated with TPP- n- ISAs. Two apoptosis hallmarks, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…We further attempted to validate the significance of the chemical/biochemical and computational predictions using a model of irradiation induced apoptosis in MECs [53] treated with TPP- n- ISAs. Two apoptosis hallmarks, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we (29,74) have developed mitochondria-targeted electron scavengers, conjugates of GS with nitroxide radicals (GS-nitroxides), capable of preventing reactive oxygen species production and CL peroxidation in mitochondria. We reasoned that GS-nitroxides may be effective in suppressing hyperoxia-induced phospholipid peroxidation in MLEC.…”
Section: Mitochondria-targeted Nitroxide (Xjb-5-131) Suppresses Hypermentioning
confidence: 99%
“…Recently, we reported that mitochondria targeted electron scavengers -hemigramicidin S conjugated nitroxides -prevented both superoxide accumulation and CL peroxidation and apoptosis initiated by ActD or irradiation without affecting Bax translocation [27,28]. Combined with the results of this work showing that Bax/Bak translocation precedes superoxide production and CL peroxidation and that genetic ablation of Bax/Bak inhibited ActD and rotenone induced CL oxidation and apoptosis, we speculate that CL peroxidation not only correlates but is likely causatively and time-dependently related to mitochondrial relocation of Bax/Bak.…”
Section: Recombinant Bax Increases Mitochondrial Peroxidase Activitymentioning
confidence: 99%